Hydrogen Production from Methanol Steam Reforming over Ce0.9Cu0.1OY Solid Solution Catalysts: The Effect of Preparation Methods - Zhang, Lirong; Wang, Yuhong; Yu, Jun; Whiting, Roger; Yi, Fengping (Asian Journal of Chemistry, 2013)
A series of Ce0.9Cu0.1OY catalysts were prepared using various methods including deposition-precipitation, conventional aqueous coprecipitation and sol-gel precipitation. The physical and chemical properties of the prepared catalysts were characterized using TEM, Raman, UV-VIS, XRD, H2-TPR and XPS techniques. These indicate that a solid solution was formed in the product. Steam reforming of methanol was carried out over Ce0.9Cu0.1OY catalysts and showed moderate methanol conversion and high selectivity to H2 and CO2. The investigation indicates that the preparative method significantly affects the active species dispersion, microstructure and the resulting catalytic performance with respect to conversion and selectivity. The Ce0.9Cu0.1OY catalyst prepared by a deposition-precipitation method displayed higher specific surface area, greater reductive ability and higher activity for methanol conversion as compared to the catalysts prepared by other methods.